Environmental decision making and risk management : selected essays - Langford, Ian H.; Turner, R. Kerry; Bateman, Ian. (Cheltenham, UK ; Northampton, MA: Edward Elgar Pub., 2004)
This memorial collection of papers represents some of the most thoughtful and innovative contributions to the literature regarding the holistic analysis of environment and health risk issues. It provides important foundations for the development of a mixed methodological approach to addressing such issues.
Includes bibliographical references.
oif 05/08/16, ijb 09/04/2019
Loan
Keywords: Environmental economics; Environmental risk assessment; Health risk assessment; Risk perception; Contingent valuation; Risk assessment